Influence of Covid-19 On China's Urban Planning and Design Regulations : A Systematic Review of Recent Policy and Regulatory Changes - World Bank (Washington, DC, 2022)
The purpose of this note is to explain how the pandemic is reshaping regulations in China and affecting urban planning and city management. In preparing this note, a meta-analysis was conducted based on a review of China’s urban planning responses to COVID-19. The review covered newly issued regulations and amendments to the existing regulations at both national and subnational levels between February and August 2020. The note identifies regulatory gaps in urban planning and provides a systematic review of how China responses to COVID-19 and addresses gaps in urban planning and building design, including emergency interventions during this crisis, and post-COVID-19 responses to build health-resilient cities. The note concludes that in response to the pandemic, Chinese authorities have issued various policies and regulations on land use, environmental management, sectoral planning, public spaces, city management, and building design for different types of buildings. This note will directly contribute to the research on health cities, one of the four pillars of the China Urban, Resilience and Land Programmatic ASA. Our objective is to document diverse practices and responses to the pandemic from different countries and offer the policymakers a handy reference that can help them plan, develop, and implement policies and regulations.